Malaysian Exploration Asset Team Strategic Case for Multi-Discipline Team - Hassan, Rozaidi (1998)
Malaysian Exploration Asset Team (MEAT) was a typical multi-discipline team in Petronas Carigali Sdn Bhd. It was formed in February 1997 with the aim to manage the company's exploration drilling operation in offshore Malaysia. MEAT is relatively a small sized team comprised a group of professionals, engineers and non-technical staffs. Its goal was to manage the operation in a safe manner, cost-effective, smooth and environmental-friendly operation. Figure 1 shows the organization chart of the team whereby it was consisted of twenty-seven members from nine different backgrounds. The team leader, who reported to the Exploration Manager, acted as the head of the operation and accountable for the overall performance of the team Based on the previous 1996/97 domestic exploration drilling programme, the overall performance of the team was satisfactorily as recomized by the management of the company. Since the team would be continually provided the same services, moreover with the increasing cost of operation, its always important for the team to analyze the environment that could affect its performance. A cost-effective operation would be the most important factor for the team, especially during the economy crisis of the country. As such, strategic management approach would be useful for the team in determining its operational strategy. From strategic point of view, a prudent strategic planning that follow a close parallel to the company's vision and objectives, would be